Effects of TiO2 addition on the phase, mechanical properties, and microstructure of zirconia-toughened alumina ceramic composite - Manshor, Hanisah; Md Aris, Suriyana; Ahmad Azhar, Ahmad Zahirani; Abdullah, Ezzat Chan; Ahmad, Zainal Arifin (Pergamon, 2014)
Ceramic composite made up of zirconia-toughened alumina (ZTA) with TiO2 as additive was constructed via a solid-state sintering route. The Vickers hardness of the obtained ZTA–TiO2 was evaluated at various levels of the TiO2 addition. Every sample was dry mixed, uniaxially pressed and sintered at 1600 1C for 1 h in a pressureless condition. The presence of TiO2 was observed to have greatly influenced the microstructure of the Al2O3. Grain growth of the Al2O3 particles was hindered with the addition of 3 wt% TiO2, but increased in size at an excess of 3 wt% TiO2. According to the results, tialite (Al2TiO5) begun appearing at a composition of ZTA–5 wt% TiO2 and this increased with the TiO2 content. The fracture toughness and hardness were enhanced from 5.93 MPa √m (0 wt% TiO2) to 6.56 MPa √m (3.0 wt% TiO2) and from 1516.13 HV (0 wt% TiO2) to 1615.8 HV (3.0 wt% TiO2), respectively. The improved bulk density from 3.9 g/cm3 (0 wt% TiO2) to 4.10 g/cm3 (3.0 wt% TiO2) resulted from the fine microstructure, thereby enhancing the mechanical properties.